Financial Performance Analysis Using Economic Value Added (EVA) in Financial Technology Sector Companies in Indonesia for the 2022–2024 Period - Lilys Suryani; Irwin Ananta Vidada (Jurnal Multidisiplin Sahombu, 2026)
This study aims to analyze the financial performance of financial technology sector companies in Indonesia using the Economic Value Added (EVA) method during the 2022–2024 period. EVA is a value-based financial performance measurement that evaluates a company's ability to generate economic value after considering the cost of capital employed. The research focuses on three companies representing the financial technology ecosystem in Indonesia, namely PT Bank Jago Tbk, PT Bukalapak.com Tbk, and PT GoTo Gojek Tokopedia Tbk, which have different business characteristics and capital structures. The study adopts a descriptive quantitative approach by calculating EVA based on three main components: Net Operating Profit After Tax (NOPAT), Invested Capital, and Weighted Average Cost of Capital (WACC) obtained from the companies’ annual financial statements. EVA is then used to determine whether the companies are able to create value for investors after covering their capital costs. The results show that during the observation period, all three companies recorded negative EVA values, indicating that their operating profits after tax were not sufficient to cover the cost of capital. However, PT Bank Jago Tbk showed relatively smaller negative EVA compared to the other companies, while PT Bukalapak.com Tbk and PT GoTo Gojek Tokopedia Tbk experienced larger negative EVA due to negative NOPAT and higher capital costs. These findings suggest that EVA provides a more comprehensive evaluation of financial performance beyond accounting profits.